ANALISIS PERBANDINGAN PENDAPATAN ANTARA PEMBAYARAN LISTRIK PASCA BAYAR DAN PRA BAYAR PADA PT. PLN (PERSERO) SULSELRABAR UP3 PAREPARE - HERLIYANA (DECISION : Jurnal Ekonomi dan Bisnis, 2020)
This study aims to determine the ratio of income between postpaid and prepaid electricity payments and to find out how the postpaid and prepaid electricity payment system at PT. PLN (Persero) Sulselrabar UP3 Parepare. The data collection techniques used in this study are, observation, interviews and documentation. The data analysis technique used in this study uses qualitative descriptive analysis to explain the postpaid and prepaid electricity payment systems, quantitative analysis techniques and comparative analysis to calculate the percentage of postpaid and prepaid income and compare income between postpaid and prepaid electricity payments. After going through the analysis process, the results show that postpaid income from 2013 - 2017 obtained a total percentage of income of 440.15% of the total number of customers of 126,641 while pre-paid from 2013 - 2017 obtained an income percentage of 59.91% of the total customer 54,626. For the postpaid electricity payment system, it can be done in two ways, namely through PPOB such as ATMs and through direct payments at the electricity payment counter that has been provided by PT. PLN (Persero) UP3 Parepare, while for prepaid electricity the payment system customers can purchase vouchers for charging electricity that can done at Alfamart, Indomaret and through the Banking mobile application.